Tmod3 Phosphorylation Mediates AMPK-Dependent GLUT4 Plasma Membrane Insertion in Myoblasts - Shrestha, Man Mohan; Lim, Chun-Yan; Bi, Xuezhi; Robinson, Robert C.; Han, Weiping (Frontiers in Endocrinology, 2021)
Insulin and muscle contractions mediate glucose transporter 4 (GLUT4) translocation and insertion into the plasma membrane (PM) for glucose uptake in skeletal muscles. Muscle contraction results in AMPK activation, which promotes GLUT4 translocation and PM insertion. However, little is known regarding AMPK effectors that directly regulate GLUT4 translocation. We aim to identify novel AMPK effectors in the regulation of GLUT4 translocation. We performed biochemical, molecular biology and fluorescent microscopy imaging experiments using gain- and loss-of-function mutants of tropomodulin 3 (Tmod3). Here we report Tmod3, an actin filament capping protein, as a novel AMPK substrate and an essential mediator of AMPK-dependent GLUT4 translocation and glucose uptake in myoblasts. Furthermore, Tmod3 plays a key role in AMPK-induced F-actin remodeling and GLUT4 insertion into the PM. Our study defines Tmod3 as a key AMPK effector in the regulation of GLUT4 insertion into the PM and glucose uptake in muscle cells, and offers new mechanistic insights into the regulation of glucose homeostasis.